The potentials of the British-Colombian trial in the Philippines. - Edra, Rolando B. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1964)
Despite its great promise as a fishing gear, midwater trawl is still untrue and unproven in many parts of the world, like the Philippines and still restricted to the exploitation of only a few species of fish principally herring, cod, sprat and mackerel. To a great extent the characteristics, behavior and biology of a particular species of fish influence the general patterns and use of the trawls. For this reason several types of midwater trawls sprung. It is worthy to note that modifications are made to adjust the gear to different kinds of environments. Present midwater trawls can be divided into two operational categories: these towed between two vessels, and these operated by a single vessel. The former was the first to be introduced on a commercial scale with the invention in 1948 of the Larson "Atom" trawl by Robert Larsen of Skagen, Denmark. The one-beat pelagic trawls have appeared on the scene since the introduction of the "Atom" trawl. Several types have been developed in different parts of the world and have received extensive publicity following operational trials and limited adoption commercially.among the most prominent are: The Larsson "Phantom" trawl, the Icelandic "Breidjerd" trawl, and the British-Columbian trawl, developed recently in Western Canada. These types also illustrate the more important variations in design and rigging of one-beat midwater trawls. The recent development of new British-Columbian trawl made this gear superior over other midwater trawls and conventional trawls. The superiority of the modified gear lies in its ability to operate alternatively on or off the sea bottom. Although the fishing tests have been carried out in a practical trial-and-error approach, the success in catching herring in midwater in commercial quantities is encouraging. In addition, the versatility of the gear permits greater flexibility in commercial operations and reduces the cost of fishing for species which habitually move between the bottom and midwater. The introduction of this gear in the Philippines may help in the exploitation of our vast aquatic resources. Under separate heading, the design, operation, advantages and disadvantages of the British-Columbian trawl, the factors governing the efficiency of midwater trawls in general, the biological factors which are necessary for the successful use of midwater trawls, and the potentialities of this dual-purpose gear in the Philippines will be discussed in detail.
Keywords: Fish capture